2007
DOI: 10.1086/516815
|View full text |Cite
|
Sign up to set email alerts
|

The Deep X‐Ray Radio Blazar Survey. III. Radio Number Counts, Evolutionary Properties, and Luminosity Function of Blazars

Abstract: Our knowledge of the blazar surface densities and luminosity functions, which are fundamental parameters, relies still on samples at relatively high flux limits. As a result, our understanding of this rare class of active galactic nuclei is mostly based on relatively bright and intrinsically luminous sources. We present the radio number counts, evolutionary properties, and luminosity functions of the faintest blazar sample with basically complete ($95%) identifications. Based on the Deep X-Ray Radio Blazar Sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
174
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(199 citation statements)
references
References 60 publications
24
174
0
1
Order By: Relevance
“…The mean redshift is calculated taking into account the effect of the sky coverage, that is each object is weighted by the inverse of the area accessible at the flux density of the source (e.g. Padovani et al 2007). …”
Section: Ve/va Analysismentioning
confidence: 99%
“…The mean redshift is calculated taking into account the effect of the sky coverage, that is each object is weighted by the inverse of the area accessible at the flux density of the source (e.g. Padovani et al 2007). …”
Section: Ve/va Analysismentioning
confidence: 99%
“…Giommi et al 1999;Padovani et al 2007). Studies performed by Massaro et al (2011b) andD'Abrusco et al (2012), based on data from the Wide-field Infrared Survey Explorer (WISE, Wright et al 2010), have shown that blazars tend to concentrate in a distinct region of the IR colour-colour diagram, known as the WISE blazar strip.…”
Section: Building a Large Sample Of Hsp Blazarsmentioning
confidence: 99%
“…For this elusive class of objects the adopted selection criteria can affect the redshift distributions of the BL Lac objects and cause different cosmological evolution scenarios (see, e.g., the discussions in Bade et al 1998 andGiommi et al 2012). Radioselected BL Lac objects seem to display a positive evolution (i.e., either the number density or the luminosity shows a decrease with cosmic time), while a negative evolution or no evolution at all was proposed for X-ray-selected objects (Rector et al 2000;Rector & Stocke 2001;Caccianiga et al 2002;Beckmann et al 2003;Padovani et al 2007;Ajello et al 2009;Giommi et al 2009Giommi et al , 2012, and references therein). A continuum trend from slightly positive-evolution low-peaked BL Lac objects to strong negative-evolution high-peaked BL Lac objects was proposed (Rector et al 2000), and was thought to be related to the X-ray to radio flux ratio (Giommi et al 1999(Giommi et al , 2012.…”
Section: Introductionmentioning
confidence: 99%